تحليل ظاهرة الغياب وعلاقته بالتحصيل الدراسي دراسة تطبيقية على طلبة كلية الاقتصاد والإدارة بجامعة القصيم بالمملكة العربية السعودية - Al-Tit, Ahmad (مجلة العلوم الإدارية و الإقتصادية, 2018)
The aim of this research was to explore the perceptions of students of the College of Business and Economics at Qassim University about the phenomenon of absenteeism, the prevalence of this phenomenon among the students, and its relationship with their academic achievement, gender and specialization. Additionally, the research aimed at identifying the reasons behind this phenomenon and how to reduce absenteeism rates. A sample was chosen consisting of (255) students, out of them (152) males and (203) females distributed to the academic departments in the college. Questionnaire consisted of (26) items was developed to measure the variables of the research, it was valid and reliable. The Research findings revealed that the percentage of students who reached the upper limit of the permitted absence rate was (14.4%), and there was a negative relationship between absenteeism among students and their academic achievement, a relationship between absenteeism and the gender of students.